PENGARUH MODEL COOPERATIVE LEARNING DAN KEPRIBADIAN (INTROVERT–EKSTROVERT) TERHADAP HASIL BELAJAR SISWA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Cooperative Learning model and student personality (introvert–extrovert) on student learning outcomes. The study used an experimental method with a 2x2 factorial design. Data analysis was performed using a two-way ANOVA test to determine the effect of each variable and the interaction between the learning model and personality. The results showed a significant effect of the Cooperative Learning model on learning outcomes, a significant effect of personality type on learning outcomes, and a significant interaction between the learning model and personality. This indicates that learning effectiveness depends on the combination of learning model and student personality type.